The New Paradigm of Physical Education: SLR Analysis of AI in Handball Measurement Tests and SDGs-Based Eco-Friendly Facilities - Dyas Andry Prasetyo (CV. Edutechnium Indonesia, 2026)
In the current era of digital transformation and global sustainability, 21st-century skills including technological literacy and environmental awareness are crucial competencies for students. Artificial intelligence (AI)-based teaching integrated with sustainability values ​​is seen as an effective, creative, and engaging pedagogical strategy to improve these skills in physical education. The background of this research is based on the limitations of previous studies, the majority of which only focused on basic manual techniques without considering the impact of infrastructure on the environment or the efficiency of data-based evaluation. This study aims to systematically analyze the literature on the role of AI in evaluating handball measurement test instruments and managing environmentally friendly infrastructure to support the Sustainable Development Goals (SDGs) targets. The method used is a Systematic Literature Review (SLR) with PRISMA design, including analysis of Scopus and ERIC databases using VOSviewer and Harzing's Publish or Perish software. The results show that AI integration has a significant positive impact on the objectivity of motor assessment and the efficiency of facility management, while scaffolding variables in teachers' digital literacy are key factors influencing the success of the implementation. The findings reveal that facilities not based on sustainability principles fail to provide long-term contributions to students' psychomotor development in a global context. In conclusion, this new paradigm demands a repositioning of the physical education curriculum that synergizes smart technology with green facility management to create an inclusive and sustainable future for sport. Keywords: Artificial Intelligence, Handball, Physical Education, Facilities and Infrastructure, Sustainable Development Goals (SDGs).